On dynamic response and damage evaluation of bridge piers under far-field explosion loads. (May 2023) - Kong, Weiming; Yang, Shanglin; Wang, Shufei; Liu, Zhicheng; Zhang, Run; Zhong, Wei; Yao, Xiaohu
Abstract: This paper aims to investigate of the dynamic response and damage mechanism of typical bridge piers under far-field explosions numerically and develop a feasible scheme for rapid damage evaluation of bridge piers. An ANSYS-AUTODYN-based explicit finite element formulation is introduced in which the dynamic input method of blast waves is developed using subroutines. The tests of drop hammer impact and far-field explosion are referenced to verify the reliability of the formulation and the mesh scale applicable to beam-column members is determined. Based on the validated formulation, the refined fluid–solid coupling models of typical single-column and double-column piers are established to explore their far-field blast responses. The effects of input parameters (i.e., the strength and angle of the blast wave, ) on the pier response are analyzed. It is demonstrated that bending damage occurs in bridge piers is similar to that of cantilever beam under different strength loads, while the damage of double-column pier members under the constant displacement increases with the increase of the blast wave angle. By incorporating the crack distribution, quantitative assessing criterion and P-I diagram, a damage evaluating scheme is proposed and the damage regularities of piers under far-field blast loads are acquired. The present work can serve as a valuable reference for blast-resistant design and damage assessment of bridge piers under far-field blast loads.